O estatuto concedido ao espaço na filosofia crítica de Kant - Souza, Islane Viana de (2024)
Based on the investigation of the two forms of knowledge proposed by Kant in his critical philosophy, namely philosophical knowledge and scientific knowledge, this dissertation aims to present an analysis of space as the foundation of the investigation in the philosophy of science. Its function is to scientifically validate mathematics and theoretical physics, particularly to examine the foundations of Euclidean geometry as instruments of physics, in addition to establishing the possibilities and limits of human knowledge. This theme arises from questioning the nature of the study of the concepts of space, mainly present in the Transcendental Aesthetic, leading to the central problem of this research: to determine whether Kant's conception of space can be understood not only from a philosophical perspective but also as part of the scientific debate. The interpretative hypotheses supporting this work are, on the one hand, the position of Michel Fichant, who argues that Kantian thought cannot be considered merely an epistemological investigation, because, in exposing the properties of space, it also engages in an ontological study, that is, a study of being itself by determining the possibilities and limitations of human thought. On the other hand, the research is closer to Gérard Lebrun's view, according to which Kant's exposition of space cannot be understood only within the philosophical realm, as his proposal engages with the sciences of his time, particularly the studies of Newton and Leibniz, thus requiring a detailed investigation of the appropriate methods for validating scientific knowledge. Therefore, drawing from both perspectives, this work intends to investigate how the scientific debate during the time of Leibniz and Newton relates to Kant’s argumentation in the Transcendental Aesthetic, which bases its examination on Euclidean geometry and Newtonian physics.